Landasan Filosofis Pendidikan Akhlak Al-Ghazali dan Ibnu Miskawaih - Ach Nurholis Majid (Fakta: Jurnal Pendidikan Agama Islam, 2022)
Recent facts state that there is a symptom of negative implications in education, there is a threat of social insecurity. These threats can be seen in immoral and immoral acts committed by school-age children and educated people. This condition is the result of the inability of the educational process in fostering the morals of the students. This moral education discourse has been widely discussed, but in a philosophical context it is necessary to refresh and explore ideas. In the context of Islamic education, the figures that can be appointed are well-known and credible Muslim figures. This article attempts to examine the philosophical foundational ideas proposed by Al-Ghazali and Ibn Miskawaih and their proposals related to ontology, epistemology, and axiology. Ibn Miskawaih and Al-Ghazali provide an understanding of morality as a mental condition that encourages a person to take an action spontaneously and consistently. Good morals, actualized in good behavior. On the other hand, bad morals will be actualized in bad behavior. Morals are indicators of a person's psyche. Al-Ghazali and Ibn Miskawaih agreed to propose a middle way. Although the terms are different. For Ibn Miskawaih, the middle way is a condition between the extreme left and the extreme right. Meanwhile, for Al-Ghazali, wasatiah is a condition of the soul that is in line with the Shari'a and reason. To achieve such conditions, training and habituation can be carried out, including efforts to approach God (Allah). The goal, said Ibn Miskawaih, so that someone can achieve as-sa'adah (happiness),